Pemberdayaan Petani Sayuran melalui Peningkatan Kesuburan Lahan, Usahatani dan Strategi Pemasaran di Desa Kenalan, Magelang - Rina Ekawati; Multi Sari Dewi; Pantjasiwi Veni Rahayu Ingesti; Minni Gunawan (Institut Pertanian Bogor, 2025)
Kenalan Village is located in the Pakis, Magelang Regency. The village occupies 3.71% of the total area in Pakis District, with topography characterized by peaks and slopes. These topographic conditions have potential for agricultural activities, especially for horticultural crops (vegetables). The fertility of land used for crop cultivation can continuously decline if it is not balanced with soil fertility improvements. Harvesting fresh vegetables alone will not be sufficient for farmers' income; therefore, a digital marketing strategy is needed to increase added value. This service activity will be carried out from June to November 2024 in Kenalan Village, Pakis District, and Magelang Regency. The service is carried out through several activities, including socialization on increasing land fertility, analysis of vegetable farming, and marketing strategies for vegetable products. Technical guidance can improve the knowledge and technology obtained, especially in knowing the fertility level of the land owned and the marketing system for vegetable products so that farmers do not rely only on sales to collectors.